The Significance and Dimension of the Dialogue in Dostoevsky - Sebastjan Kristovič; Urša Zabukovec (Edinost in Dialog, 2021)
Dialogue in Dostoevsky does not mean simple communication, as we generally understand this notion today. In modern times, we often understand dialogue in the senseof rhetorical persuasion, which is always based on one or another power and with which we want to convince others of our right, our truth as the only one correct. When others do not accept this »absolute truth« possessed by someone or a group, we are a step away from imposing this truth, which always includes the threat of force and consequently means a degradation of human dignity and personal freedom. The article presents the meaning and understanding of dialogue in Dostoevsky's works through the phenomenological-hermeneutic and analytical-synthetic methods. Dostoevsky opens a new dimension to the understanding of dialogue, which is in constitutive connection to be by understanding freedom, love, identity, beauty, faith, and meaning. »To be« (lat. existere) in Dostoevsky means »to be in dialogue«. In this sense, dialogue has an anchor at the ontological level and belongs to order of love (ordo amoris). But love is not some current mood or some emotional ecstasy, it is the basic principle of existence, action and life. In this context, love is the culmination of dialogue. The paradigm of dialogue in Dostoevsky thus represents the modus operandi of universal dialogue. Undoubtedly, the key concept that will fundamentally mark the common future of humanity and the earth is precisely »dialogue«. Dostoevsky's attitude towards Jews is markedly ambivalent. This isn’t really surprising, since ambivalence is written into the very DNA of Dostoevsky and his work. The writer resolves the ambivalence of the complex »Jewish question« on a genuinely dialogical level, the constitutive element of which is active love.